Effect of Te doping on the thermopower of PbSe1–xTex. Issue 6 (November 2012) - Basu, Ranita; Bhattacharya, S.; Bhatt, Ranu; Singh, Ajay; Aswal, D. K.; Gupta, S. K.
Abstract : The authors have studied the effect of Te doping on structural, morphological and thermopower of PbSe for the composition of PbSe1–x Tex (x = 0·0, 0·2, 0·50, 0·75, 0·9 and 1·0). The samples were prepared using melting and rocking. The scanning electron microscopy indicated that all the samples have lamellar morphology. The X-ray diffraction analysis suggested that the lattice parameter increases linearly with dopant concentration (x). The temperature dependence of thermopower measured for samples having different x revealed unusual increase in thermopower for the composition x = 0·5, for example, at 427°C, and the thermopower values for PbSe0·5 Te0·5, PbTe and PbSe were 292, 188 and 134 μV/K, respectively. A dramatic thermopower enhancement for PbSe0·5 Te0·5 is attributed to scattering of the majority charge carriers by the defect sites.